2017
DOI: 10.1016/j.watres.2017.07.049
|View full text |Cite
|
Sign up to set email alerts
|

The public health significance of latrines discharging to groundwater used for drinking

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Faecal contamination of groundwater from pit latr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Additionally, subsurface infiltration from new pit latrines is higher during the initial few months and diminishes afterward, potentially due to the formation of a layer (like the schmutzdecke on biosand filters) that attenuates contamination. 47 Finally, while E. coli typically survives <20 days in soil, 49 it can persist for extended durations in tropical soils. 50 It is therefore possible that a longer follow-up period would capture more pronounced impact from sanitation improvements on environmental contamination.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, subsurface infiltration from new pit latrines is higher during the initial few months and diminishes afterward, potentially due to the formation of a layer (like the schmutzdecke on biosand filters) that attenuates contamination. 47 Finally, while E. coli typically survives <20 days in soil, 49 it can persist for extended durations in tropical soils. 50 It is therefore possible that a longer follow-up period would capture more pronounced impact from sanitation improvements on environmental contamination.…”
Section: Resultsmentioning
confidence: 99%
“…Microbiological contamination of groundwater provides the clearest indicator of pollution by animal and/or human organic waste, and even small amounts of contamination pose a significant public health risk (Howard, et al, 2003, Ravenscroft, Mahmud, Islam, Hossain, Zahid, Saha, Zulfiquar Ali, Islam, Cairncross, Clemens andIslam, 2017). This enhanced risk is reflected in the zero MPN/100ml limit for bacteria in drinking water (WHO, 2011).…”
Section: 4 Microbiological Parameters -E Coli and Total Coliformmentioning
confidence: 99%
“…Ravenscroft et al (2017) used a carefully controlled study to document sources and contributions of fecal contaminants through a latrine-aquifer-well-user system, and proposed a four-component conceptual model. Of the four contaminant pathways (leakage of bacteria through the latrineaquifer interface; leachate migration to the borehole; transport through and contamination of the well equipment; contamination of the drawn water), they concluded that leakage from pit latrines contributes little to the disease burden beyond a latrine-well spacing of c.10 m; rather, they emphasized the importance of recontamination at the well, and between the well and the user, from non-latrine sources.…”
Section: 4 Microbiological Parameters -E Coli and Total Coliformmentioning
confidence: 99%
“…Unsanitary toilets are a threat to the environment [1][2][3][4][5][6] and public health [5,[7][8][9][10][11][12]. Recognizing this fact, the Chinese government inaugurated the toilet revolution to improve unsanitary toilets in rural areas in October 2014.…”
Section: Introductionmentioning
confidence: 99%